2016
DOI: 10.4081/vl.2016.5992
|View full text |Cite
|
Sign up to set email alerts
|

Compression and sports

Abstract: Not available

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Moreover, there is a disparity in performance between the use of commercially developed certified graduated compression products and stockings generally used during physical exercise or sport. 7 The available literature is showing a positive effect of compression garments mainly on the delayed onset of muscle soreness, without reporting significant data regarding the required compression features in terms of pressure and stiffness. [8][9] Importantly, studies published more than 70 years ago reported a significant decrease in ambulatory venous pressure by walking, suggesting the activation of the muscle pump improving lower limb drainage.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there is a disparity in performance between the use of commercially developed certified graduated compression products and stockings generally used during physical exercise or sport. 7 The available literature is showing a positive effect of compression garments mainly on the delayed onset of muscle soreness, without reporting significant data regarding the required compression features in terms of pressure and stiffness. [8][9] Importantly, studies published more than 70 years ago reported a significant decrease in ambulatory venous pressure by walking, suggesting the activation of the muscle pump improving lower limb drainage.…”
Section: Introductionmentioning
confidence: 99%
“…13 Compression seems to have positive effects also in healthy people practicing sports. These aspects are underlined in the paragraphs by Jean Patrick Benigni 14 and Helmut Lötzerich. 15 Finally, Bender and co-authors present interesting data on a completely obscure indication for compression represented by the restless leg syndrome.…”
mentioning
confidence: 99%